Cripping Sex Work: Disabled Sex Workers and Racialized Disgender in the Online Sex Industry - Shawna Felkins (Disability Studies Quarterly, 2022)
This paper explores how disabled online sex workers experience “racialized disgendering” in social media spaces and content platforms and introduces a new framework for “cripping sex work.” After discussing how disabled sex workers experience crip time and their bodyminds while navigating labor demands in the online industry, this paper argues for a shift away from the neoliberal “empowerment” discourse in much research and activism related to sex work. And demonstrates how white and otherwise privileged sex workers benefit from and uphold systems of power that financially benefit them through sexual gentrification, while multiply marginalized sex workers experience cyberviolence and microaggressions at the hands of other sex workers. My analysis uncovers specific ways that racialized disgendering impacts sex workers with disabilities and argues for the importance of mutual aid and paying sex workers for their labor, culminating in a list of tangible action steps for privileged sex workers.
Keywords: sex work; racialized disgender; fetishization; labor; crip; online; gig economy